Implikasi Pendidikan Keagamaan Terhadap Moderasi Beragama di SMTK Marturia Sentani Kabupaten Jayapura Tahun 2022 - Hendrik Belwawin; Fransina O Abineno (Populis : Jurnal Sosial dan Humaniora, 2023)
Religious moderation is not only limited to the scope of cognition, but the essence of it requires a moderate attitude in form of action. This study tries to find out the implications of religious education on religious moderation in SMTK Maturia Sentani. The method used in this study was descriptive qaulitaive. The samples of this study were taken from 18 students of twelth grade and 14 teachers. Techniques in collecting data were applied by questionnaires and in-depth interviews. To analyze the data, firstly the percentage of each indicator of religious moderation is carried out such as national commitmen, tolerance, the way of peace, cultural accommodation, and the implications of Christian religious education. Then the percentage results are compared with the interview results as a form of confirmation. The results of this study reveal that students have a high national commitment, prioritize the attitude of peaceful way such as deliberation, dialogue, and do local wisdom as cultrural acomodation for bridging the peaceful like “bakar batu”. However, this study also found or detected the indicator of early radicalism in students. The form of radicalism is not accepting the existence of other groups or religions in their environment and feeling uncomfortable living side by side with other religions. Related to curriculum to support religious moderation, the subject of religious moderation can be included into active curriculum to suppress the emergence of exclusive views.Moderasi beragama tidak hanya sebatas pada ranah kognisi saja, tetapi hekekat dari moderasi beragama membutuhkan sikap yang moderat yaitu berupa tindakan. Penelitian ini berusaha melihat implikasi pendidikan keagamaan terhadap moderasi beragama pada siswa SMTK Maturia Sentani. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Sampel dalam penelitian ini adalah 18 siswa yang diambil dari siswa kelas XII dan 14 guru tetap. Teknik dalam mengumpulkan data adalah melalui kuisioner dan wawancara mendalam. Untuk menganalisa data pertama dilakukan persentase pada masing-masing indikator moderasi beragama seperti komitmen kebangsaan, toleransi, jalan damai, akomodasi budaya, dan implikasi pendidikan agama Kristen. Kemudian hasil persentase tersebut disandingkan dengan hasil wawancara sebagai bentuk konfirmasi. Hasil dari penelitian ini menunjukkan bahwa siswa mempunyai komitmen kebangsaan yang tinggi, mengutamakan sikap jalan damai seperti musyawarah, dialog dan yang bersifat kearifan lokal sebagai akomodasi budaya seperti “bakar batu”. Namun penelitian ini juga menemukan atau mendeteksi bibit radikalisme pada siswa. Bentuk sikap radikalisme pada beberapa siswa adalah tidak menerima keberadaan kelompok/agama lain di lingkungan mereka dan merasa tidak nyaman hidup berdampingan dengan agama lain. Implikasi pendidikan keagamaan  menyarankan mata pelajaran moderasi agama termuat dalam kurikulum untuk menekan munculnya pandangan ekslusif.